Trubarjev in Dalmatinov svetopisemski prevod po vzoru Lutrove prevajalske strategije »rem tene, verba sequentur« - Kučiš, Vlasta (Slavia Centralis, 2020)
Trubar’s and Dalmatin’s translations of the Bible according to Luther’s translation strategy “rem tene, verba sequentur” The Middle Ages is considered to be one of the darkest periods in the history of humanity. Hence, in this period, vernacular translations of the Bible contributed to the beginning of European multilingual and intercultural dialogue. Luther’s Bible translation is an important milestone in the development of today’s global information culture, since it meant that the word of God had become accessible to anyone who was able to read. In the Middle Ages, science and education developed in the shadow and under the dominance of theology, which was clerically oriented and exclusively advocated Christianity as the leading culture. Luther’s revolutionary view of the translation “rem tene, verba sequentur” (summarize the content, the words will follow) corresponded to the Protestant translation strategy, which marked Luther, Trubar and Dalmatin’s Bible translations and, at the same time, represented one of the fundamental principles of reformation as an important political-cultural movement in Europe. In the empirical part of the study, we will analyse Dalmatian’s Bible translation, define translation strategies and compare this translation to translations by Luther and Trubar.
Keywords: translation; Bible; reformation; multilingualism; Index librorum prohibitorum